Back to Qumran : final report (1993-2004) - Magen, Izchak; Peleg, Yuval (Judea and Samaria Publications (Series), 2018)
The renewed excavations at Qumran began in 1993, as part of Operation Scroll. In this project, implemented in cooperation with the Israel Antiquities Authority, hundreds of caves were surveyed. The survey began in the area north of Jericho, and continued along the length of the fault scarp that meets the Dead Sea, as far as En Gedi.